2015
DOI: 10.1111/jmg.12148
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for protracted prograde metamorphism followed by rapid exhumation of the Zermatt‐Saas Fee ophiolite

Abstract: Major and trace-element zoning in garnet, in combination with Rb-Sr, Sm-Nd and Lu-Hf geochronology, provide evidence for a protracted garnet growth history for the Zermatt-Saas Fee (ZSF) ophiolite, western Alps. Four new Lu-Hf ages from Pfulwe (c. 52-46 Ma) and one from Chamois (c. 52 Ma) are very similar to a previously published Lu-Hf age from Lago di Cignana. Overall, the similarity of geochronological and garnet zoning patterns suggests that these three localities had a similar prograde tectonic history, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 96 publications
(167 reference statements)
2
30
0
Order By: Relevance
“…Recently, part of the Monviso ophiolite has been interpreted as forming a single unit with the ZSZ, that would consist of a continuous slab recording a coherent metamorphic evolution (Angiboust et al ., ). In contrast with the last interpretation, the age data indicate a wide time interval of re‐equilibration during subduction of the ZSZ rocks and associated continental slivers between 80 and 40 Ma (with ages interpreted as referred to peak conditions comprised between 58 and 38 Ma; Skora et al ., , ; Springer et al ., ; Weber et al ., and references therein) consistent with indications of a heterogeneous metamorphic evolution.…”
Section: Geological Settingmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, part of the Monviso ophiolite has been interpreted as forming a single unit with the ZSZ, that would consist of a continuous slab recording a coherent metamorphic evolution (Angiboust et al ., ). In contrast with the last interpretation, the age data indicate a wide time interval of re‐equilibration during subduction of the ZSZ rocks and associated continental slivers between 80 and 40 Ma (with ages interpreted as referred to peak conditions comprised between 58 and 38 Ma; Skora et al ., , ; Springer et al ., ; Weber et al ., and references therein) consistent with indications of a heterogeneous metamorphic evolution.…”
Section: Geological Settingmentioning
confidence: 97%
“…For temperatures <550°C, lawsonite, which was detected in the Valtournanche metabasite as relicts replaced by paragonite, epidote and minor albite (e.g. Skora et al, 2015), has been never observed in the rodingites, even if it is predicted to be stable at these temperatures. For temperatures >580°C and up to 680°C, most of the rodingite compositions are characterized by assemblages involving different modal amounts of diopside, chlorite, garnet, epidote and rutile.…”
Section: Chl Grt Tlc Ep Rtmentioning
confidence: 99%
“…Exhumation of the subducted metaophiolites of the Western Alps occurred in a time span ranging between ca. 42 and 36 Ma (e.g., Beltrando et al, ; Gouzu et al, ; Reddy et al, ; Skora et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Zermatt-Saas zone has been affected by eclogite facies metamorphism (P~25-30 kbar and T~550-600°C: Bucher et al, 2005) dated at ca. 40-50 Ma (Amato et al, 1999;Dal Piaz et al, 2001;Lapen et al, 2003;Rubatto, Gebauer, & Fanning, 1998;Skora et al, 2015). Moreover, in the Lago di Cignana area, it recorded ultrahigh pressure conditions (i.e., Lago di Cignana unit; T = 615 ± 15°C and P = 28 ± 10 kbar: Reinecke, 1998; T = 600°C and P ≥ 32 kbar: Frezzotti, Selverstone, Sharp, & Compagnoni, 2011).…”
Section: The Axial Belt Of the Western Alps: Geological Frameworkmentioning
confidence: 97%